1994
DOI: 10.1042/bj3010585
|View full text |Cite
|
Sign up to set email alerts
|

Expression of transcobalamin II mRNA in human tissues and cultured fibroblasts from normal and transcobalamin II-deficient patients

Abstract: Transcobalamin II (TCII) is an important plasma transporter of cobalamin (Cbl; vitamin B12). In the present study, TCII gene expression in human and rat tissues and in the fibroblasts of patients with TCII deficiency was investigated. Northern-blot analyses revealed expression of TCII mRNA in many human and rat tissues. In humans, this was 14-fold higher in the kidney than in liver, whereas in the rat the levels of expression were similar in the kidney and liver. Southern-blot analysis of genomic DNA from seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…It is suggested to be a homodimer with an estimated size of 120-130 kDa (35) as judged by SDS/gel electrophoresis. The protein has also been detected by immunoblotting of isolated rat Mg2+-precipitated kidney basolateral membranes (40), and this (5,6,8,10,12) showing that the proportional uptake in the kidney of dietary B12 or intravenously administrated TC-B12 is higher at a high B12 load in the organism (5,6,8,12 were reported to inhibit the binding to this receptor, which might be identical to megalin. The binding of both the apo-and holo TC seems biological meaningful, because binding of only the holoform would result in loss of TC in the urine.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is suggested to be a homodimer with an estimated size of 120-130 kDa (35) as judged by SDS/gel electrophoresis. The protein has also been detected by immunoblotting of isolated rat Mg2+-precipitated kidney basolateral membranes (40), and this (5,6,8,10,12) showing that the proportional uptake in the kidney of dietary B12 or intravenously administrated TC-B12 is higher at a high B12 load in the organism (5,6,8,12 were reported to inhibit the binding to this receptor, which might be identical to megalin. The binding of both the apo-and holo TC seems biological meaningful, because binding of only the holoform would result in loss of TC in the urine.…”
Section: Discussionmentioning
confidence: 97%
“…For the SPR analyses, the BlAcore sensor chips (type CM5, Pharmacia) were activated with 1:1 mixture of 0.1 M N-ethyl-N'-(3-diethylaminopropyl) carbodiimide and 0.1 M N-hydroxysuccimide in water. Rabbit megalin and human a2MR/LRP were then immobilized at a concentration of 40 ,ug/ml in 10 mM sodium acetate (pH 4.5 and pH 3.0), respectively, and the remaining binding sites were blocked with 1 M ethanolamine (pH 8.5). The SPR signal from immobilized receptors generated 9,000-18,000 of the mass equivalent BIAcore response units.…”
Section: Methodsmentioning
confidence: 99%
“…It is highly unlikely that Cbl transport bound to TC II occurs physiologically bypassing the well accepted IF/IFCR pathway of Cbl transport (26) for the following two reasons. 1) TC II, the ligand has never been detected in the gastrointestinal lumen despite the recent finding of relatively high levels of TC II mRNA in human pancreas (27). However, it is not known whether TC II like IF in some species (28) is secreted from the pancreas and mediate luminal uptake of Cbl via TC II-R. 2) patients with inherited disorders (29,30) of IF or IFCR develop Cbl deficiency, suggesting that IF/IFCR-mediated Cbl transport system is the only physiologically operational intestinal uptake system for Cbl transport in man.…”
Section: Discussionmentioning
confidence: 99%
“…TC II gene is expressed in many types of cells and tissues but at different levels (2). Increased levels of plasma TC II have been reported in patients with a variety of diseases (3), indicating that the TC II gene may have a basal expression in many cells, but could be induced under some pathological conditions.…”
Section: Human Transcobalamin II (Tc Ii)mentioning
confidence: 99%
“…Lack of expression or expression of defective forms of TC II leads to the development of intracellular cobalamin deficiency (4). Recent studies (2,5,6) from our laboratory have shown that in the most common form of TC II deficiency, lack of immunoreactive plasma TC II is due to lack of TC II protein synthesis, which in turn is due to extremely low levels of TC II mRNA (2). Although in many patients studied the great reduction of TC II mRNA is due to nonsense mutations (5,6), or to DNA deletions (6), available evidence suggests that TC II deficiency can also result from promoter defects (5).…”
Section: Human Transcobalamin II (Tc Ii)mentioning
confidence: 99%